PROBLEM OF FORMING BALANCED AGROINNOVATION SYSTEMS: EMPIRICAL EVIDENCE FROM RUSSIAN REGIONS - Yuri PREOBRAZHENSKIY; Anna FIRSOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper studied the issues of the balanced spatial development of agro innovation systems of Russian regions using the main indicators of agricultural innovation for 2015-2019: innovative products in crop and livestock production, agricultural machinery, as well as graduates of agricultural universities and employed in the agricultural sector. The degree of concentration of these indicators was determined using the Herfindahl-Hirschman index for the regions of Russia. The results reveal a high of concentration of costs of technological innovations in the agro production, when from 50% to 90% of the costs of the technological innovation in the crop and livestock sectors are concentrated in only 2-3 Russian regions, as well as the absence of dependence on the production of innovative agricultural products on the degree of concentration of indicators and a balanced ratio in the labor market of agricultural specialists in the regions of Russia. To ensure progressive structural changes and enhance innovative activity in regional AIS and increase the efficiency of agriculture, measures are proposed to enhance the balance of AIS components and spillover effects of innovations, resulting in an increase in the efficiency of agro innovation systems functioning.